PENGARUH STRATEGI BISNIS TERHADAP TAX AVOIDANCE DENGAN SUSTAINABILITY PERFORMANCE SEBAGAI VARIABEL INTERVENING - Ai Hendrani; Mochamad Alvi Adhitia; Dihin Septyanto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of business strategy on tax avoidance with sustainability performance as an intervening variable in manufacturing companies. The population in this study is the manufacturing sector companies listed on the IDX in 2015-2019. The research sample was taken using purposive sampling method. Obtained 70 samples. This study uses multiple regression analysis. In this study, Business Strategy is measured using EMP/SALES, Market to Book Ratio, Maket,&PPEINT, sustainability performance is measured using Investment in research and development, tax avoidance is measured using Effective Tax Rate.Based on the results of data analysis, it can be concluded that: (1) business strategy has a positive effect on sustainability performance. (2) business strategy has no effect on tax avoidance. (3) sustainability performance has a negative effect on tax avoidance. (4) sustainability performance can mediate the effect of business strategy on tax avoidance. This result is consistent across several measures of tax avoidance